Marketing of biomove 3000 : exploratory research in factors affecting willingness to buy/try portable stroke rehabilation machine & marketing plan. - Chen, Peiqi. (2008)
The primary objectives of this project was to find out consumers’ willingness to accept unsupervised and self administered after-stroke rehabilitation and to prepare a detailed marketing plan for Biomove 3000 machine in Singapore.